Artificial Confinement and Process: A Visual Analysis of the Impact of Exhausted Space on the Human Condition - Hillstead, Chris John (Curtin University, 2020)
This practice-led research project investigates the prison space from an insider’s perspective through the mediums of drawing and digital manipulation. Literature on the daily happenings within the closed society of those incarcerated remains scarce. My examination offers a rare insight into the lived experiences and the effects of isolation, and redresses the imbalance of the prisoner, as an informed stakeholder, in the justice debate. In Western Australia, mobility in closed institutions is severely restricted, and geography is confined to a harsh space. Over many years, the ontological make-up of an individual has the potential to be further damaged or become unhinged. One such phenomena inherent to long-term incarceration is the experience of ‘limited depth perception’, which is a result of restricted movement within the prison estate. My research interrogates the impact the spatial tension induced by the effects of limited movement by using the visual mediums of drawing, digital manipulation and print process. This project has been developed in two phases. The first phase explores how limited agency within the carceral boundary impacts on the human condition and has the ability to initiate change through the anti-portrait. By incorporating the findings from the first phase, the second phase investigates how art can offer a positive resistance to the effects of imprisonment and isolation from society. This project develops a reflexive narrative in the form of a ‘prisoner voice’. Essentially, this voice will provide anecdotal evidence of the lived experience I incur on a daily basis and my struggle to resist the power imbalance of being exposed to an environment of control. Prisoners have limited opportunities to utilise their time in a productive manner to counter the negative effects of incarceration, yet some offenders cultivate a robust intellectual life as a form of resistance and, indeed, for survival. The act of exhibiting artwork in society tests the porosity and liminality of the prison boundary as a form of leakage that makes the prisoner visible to the free-world. This research highlights the need for prisoners to utilise time in a more efficient way; to insulate against the deleterious effects of isolation; and to develop the appropriate skills to become ‘good citizens’.